Reducing Nitrogenous Waste in RAS culture of GIFT Fingerlings Through Dietary Manipulation of Protein and Lipid Levels - Mannur, Vijayakumar Sidramappa; Kumar, Sikendra; Varghese, Tincy; Satyakumar, Akhila; Sardar, Parimal; Deo, Ashutosh D; Kumar, H Sanath; Patel, Anusha; Mohanta, Kedar Nath (Fishery Technology, 2025)
Recirculating aquaculture systems (RAS) offers several advantages, such as increased production and water conservation, but they can lead to elevated nitrogenous waste levels due to their intensive nature. This 60-day feeding trial investigated the effects of six hetero-nitrogenous and hetero-caloric diets on genetically improved farmed tilapia (GIFT) fingerlings reared in RAS. Six diets, with decreasing crude protein from 40% to 30% and increasing lipid levels from 7% to 12% were formulated and designated as: T1 (40% CP, 7% lipid), T2 (38% CP, 8% lipid), T3 (36% CP, 9% lipid), T4 (34% CP, 10% lipid), T5 (32% CP, 11% lipid), and T6: 30% CP, 12% lipid). GIFT fingerlings (initial weight 5.05 ± 0.03 g) were stocked evenly into eighteen RAS tanks, maintaining stocking density of 6000 g/m3. Results showed a significant (p < 0.05) reduction in total ammonia-nitrogen, nitrite-nitrogen (NO2-N), and nitrate-nitrogen (NO3-N) levels in the culture water from T1 to T6. However, phosphorus (PO43-) levels did not show a significant difference (p > 0.05) among the different treatment groups. The gill superoxide dismutase (SOD) and catalase (CAT) activities, indicators of oxidative stress, were elevated (p < 0.05) in T5 and T6, while liver CAT activity, crucial for hydrogen peroxide detoxification, also increased significantly (p < 0.05). The T4 group (34% CP, 10% lipid) exhibited significantly (p < 0.05) higher specific growth rate and lower NH3-N, NO2-N, and NO3-N levels compared to other groups. Therefore, a diet of 34% CP and 10% lipid is recommended for GIFT fingerlings in RAS to promote growth and to minimise nitrogenous waste.